The Role of Food Product Packaging Labels on Product Purchase Interest - Noviarama Dwi Prayusi; Eka Andriani (Universitas Negeri Malang, 2022)
Excellent and correct labeling is needed to support a food product. However, not all producers, such as small and medium enterprises (MSMEs), can implement it. In this study, the researcher used the literature study method. The method was employed to collect the related data from various sources, such as journals, books, and other types of literature. Thereby, the data can be presented as further research descriptions. In addition, the data unveiled that labels did not only convey information but also served as advertising and product branding. Excellent labeling helped consumers to choose the needed products. Thus, the role of food labeling is significant. Labels also played a role in educating the public and boosted the product's value. Likewise, labeling could be an attractive marketing strategy to increase products' competitiveness. Inexorably, glamorous packaging could attract consumers' attention and ultimately seduce them to buy the product.